PENGARUH PROFESIONALISME DAN PENDIDIKAN TERHADAP PENGUATAN KOMPETENSI PRAJURIT KORPS MARINIR - La Ode Rustam Balemping; Trianggo Budi Sukarso; Edi Irawan Bangun (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
The Marine Corps has a position as the Main Operations Command for the Indonesian National Army and the Main Command for Development at the Navy Headquarters. The purpose of this study was to see how the influence of each variable on strengthening the competence of soldiers and how the effect simultaneously. The number of samples in this study were 87 respondents with the technique used to determine the sample, the researcher used a simple random sampling technique. And for data processing researchers assisted with software SPSS 25.0 for windows. The results obtained in data processing are the tcount value on the Professionalism variable of 2.454 and Education obtained by 6.938 while the t table obtained is 1.663. So it can be interpreted that there is an influence between Professionalism and Education partially on the Competence of Soldiers, so that the conclusion is H0 is rejected and H1 is accepted. And the value of fcount on the variables of Professionalism and Education obtained is 51,796 while ftable is 3.107. So it can be interpreted that there is an influence between Professionalism and Education simultaneously on the Competence of Soldiers. So the conclusion is H0 is rejected and H1 is accepted.